THE INFLUENCE OF ROBOT DANBO MEDIA ON THE MATHEMATIC REPRESENTATION ABILITY OF PRIMARY SCHOOLS - Hani Handayani (Widyagogik, 2020)
The background of the problem in this study is the low mathematical representation ability of class V students. The media used to improve students' mathematical representation abilities is using the robot danbo  media. volume of cubes and blocks in grade V students. This study aims to determine the effect of using danbo robot media on the mathematical representation ability of class V students in learning the volume of cubes and blocks in class V. The research method used is the one group pretest-posttest design method (one group pretest-posttest design) in Class V students. This research data was collected through the pretest and posttest scores of mathematical representation abilities with a total of 6 students, after being treated using the robot danbo media. The ability of students' initial understanding before treatment (pretest) obtained an average value of 65.3 while after treatment (posttest) was 86.1. It can be seen from the results of data processing using the t test with a confidence level of 95% (α = 0.05). It can be seen that the tcount is 3.4 and the ttable is 2.5706. So that H_0 is rejected, meaning that there is an effect of using danbo robot danbo media on the mathematical representation ability of the volume of blocks and cubes in class V.